CXCR6 Expression Is Important for Retention and Circulation of ILC Precursors - Sylvestre Chea; Cécilie Possot; Thibaut Perchet; Maxime Petit; Ana Cumano; Rachel Golub (Mediators of Inflammation)
Innate lymphoid cells are present at mucosal sites and represent the first immune barrier against infections, but what contributes to their circulation and homing is still unclear. Using Rag2−/−Cxcr6Gfp/+ reporter mice, we assessed the expression and role of CXCR6 in the circulation of ILC precursors and their progeny. We identify CXCR6 expressing ILC precursors in the bone marrow and characterize their significant increase in CXCR6-deficient mice at steady state, indicating their partial retention in the bone marrow after CXCR6 ablation. Circulation was also impaired during embryonic life as fetal liver from CXCR6-deficient embryos displayed decreased numbers of ILC3 precursors. When injected, fetal CXCR6-deficient ILC3 precursors also fail to home and reconstitute ILC compartments in vivo. We show that adult intestinal ILC subsets have heterogeneous expression pattern of CXCR6, integrin α4β7, CD62L, CD69, and CD44, with ILC1 and ILC3 being more likely tissue resident lymphocytes. Intestinal ILC subsets were unchanged in percentages and numbers in both mice. We demonstrate that the ILC frequency is maintained due to a significant increase of ILC peripheral proliferation, as well as an increased proliferation of the in situ ILC precursors to compensate their retention in the bone marrow.